2001
DOI: 10.1152/ajpregu.2001.281.1.r115
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to leptin in obese db/db mice are strain dependent

Abstract: Obese, diabetic C57BL/Ks db/db mice that lack the long-form leptin receptor exhibit no decrease in body weight or food intake when treated with leptin. Here we compared responses to leptin in two strains of db/db mice: C57BL/6J mice that are hyperglycemic and hyperinsulinemic and C57BL/Ks that are hyperglycemic and normo- or hypoinsulinemic. Chronic intraperitoneal infusion of 10 microgram leptin/day partially reversed hyperglycemia in C57BL/6J male mice but exaggerated the diabetic state of female mice. Bolus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…Others have suggested that the short-form receptors act as transport proteins, facilitating passage of leptin into the brain (15). Recently we have shown that BL/6J db/db mice, which do not express the longform leptin receptor, are metabolically responsive to leptin administered peripherally (19), suggesting that short-form receptors have a function beyond that of a transport protein. It does not appear, however, that the failure of BL/3J db/db mice to accurately compensate for lipectomy as quickly as the other genotypes of mice in experiment 2 is due to either a decreased energy intake or an increased thermogenesis compared with BL/6J db/db mice, because food intakes and rectal temperatures are not different between genotypes (Harris, unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
“…Others have suggested that the short-form receptors act as transport proteins, facilitating passage of leptin into the brain (15). Recently we have shown that BL/6J db/db mice, which do not express the longform leptin receptor, are metabolically responsive to leptin administered peripherally (19), suggesting that short-form receptors have a function beyond that of a transport protein. It does not appear, however, that the failure of BL/3J db/db mice to accurately compensate for lipectomy as quickly as the other genotypes of mice in experiment 2 is due to either a decreased energy intake or an increased thermogenesis compared with BL/6J db/db mice, because food intakes and rectal temperatures are not different between genotypes (Harris, unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
“…Understanding the overall biological etiology of obesity will require 1973; Harris et al 2001;Hofmann et al 2001). That is, different alleles of genes other than the knockout or identification of genes responsible for each of these different mechanisms.…”
mentioning
confidence: 99%
“…These epistatic interactions likely influence many complex diseases, with obesity as a clear example (17)(18)(19). Evidence that epistasis is common in obesity has been derived from statistical analyses (20), but it is also apparent from the almost universal observation that obesity phenotypes of knockout and spontaneous mutant mice are dependent on the background mouse strain on which the mutations are placed (21)(22)(23)(24). That is, different alleles of genes other than the knockout or mutant gene present in different mouse strains interact with (are epistatic with) the knockout or mutation to produce the phenotype.…”
mentioning
confidence: 99%